Pengaruh Media Sosial dan Fear Of Missing Out (FOMO) terhadap Keputusan Pembelian Produk Fashion pada Kalangan Generasi Z di Kota Singaraja - Ketut Anggarawati; I Wayan Suwendra (Ekuitas: Jurnal Pendidikan Ekonomi, 2026)
This study aims to determine the influence of social media on Fashion product purchasing decisions, to determine the influence of Fear Of Missing Out (FOMO) on Fashion product purchasing decisions, and to determine the simultaneous influence of social media and Fear Of Missing Out (FOMO) on Fashion product purchasing decisions among Generation Z in Singaraja City. The sampling technique used in this study was purposive sampling, with a total sample of 120 Generation Z respondents in Singaraja City. This study employed a quantitative method with data collection techniques conducted through questionnaires and analyzed using multiple linear regression. The data were processed using SPSS version 25, which showed that (1) social media partially had a positive and significant effect on Fashion product purchasing decisions, (2) Fear Of Missing Out (FOMO) partially had a positive and significant effect on Fashion product purchasing decisions, and (3) simultaneously, the variables of social media and Fear Of Missing Out (FOMO) had a positive and significant effect on Fashion product purchasing decisions among Generation Z in Singaraja City.